The role of altered microRNA expression in premalignant and malignant head and neck lesions with epithelial origin. Issue 6 (6th November 2022) - Farshbaf, Alieh; Mohajertehran, Farnaz; Sahebkar, Amirhossein; Garmei, Yasaman; Sabbagh, Parisa; Mohtasham, Nooshin
Abstract: Background and Aims: The premalignant lesions of the oral cavity carry a risk of transformation to malignancy. Hence, early diagnosis followed by timely intervention remarkably affects the prognosis of patients. During tumorigenesis, particular microRNAs (miRNAs) show altered expressions and because of their post transcriptionally regulatory role could provide favorable diagnostic, therapeutic, or prognostic values in head and neck cancers. Methods: In this review, we have demonstrated diagnostic, prognostic, and potential therapeutic roles of some miRNAs associated with oral premalignant and malignant lesions based on previous validate studies. Results: It is previously documented that dysregulation of miRNAs contributes to cancer development and progression. MiRNAs could be tumor suppressors that normally suppress cell proliferation, differentiation, and apoptosis or play as oncogenes that improved tumorigenesis process. Altered expression of miRNAs has also been reported in premalignant oral epithelial lesions such as leukoplakia, oral submucous fibrosis, oral lichen planus and some malignant carcinoma like oral squamous cell, verrucous, spindle cell, Merkel cell carcinoma and basal cell. Conclusion: Some of miRNAs could be new therapeutic candidates in miRNA‐based target gene therapy. Although more investigations are required to identify the most favorable miRNA candidate, altered expression of some miRNAs could be used as biomarkers in premalignant lesions and oral cancers with high sensitivity and specificity.